Using Urban Farmer Perceptions of Urban Agricultural Resources to Inform Extension Programming: A Q Methodology Study - Joshua Campbell; Angel N Riggs; Diane Montgomery (Journal of Applied Communications, 2023)
Urban farmers face challenges as they work among traditionally underserved populations, are new to farming, and may not recognize the resources available to them. The United States Department of Agriculture (USDA) prioritizes urban food production research and has recognized the unique challenges faced by urban farmers. The purpose of this study was to better understand the perspectives of urban farmers toward urban agricultural resources. Using the USDA Urban Agricultural Toolkit (2016) as a conceptual framework, this study found three perspectives of Oklahoma agricultural producers regarding urban agricultural resource challenges: The Visionary Farmer, The Business-minded Farmer, and The Learning Farmer. Visionary Farmers emphasize the application of urban agriculture toward urban social and community-building needs. Business-minded Farmers recognize the need for economic and financial education and resources for urban farmers. Learning Farmers highlight the need for continued agricultural education in urban agricultural operations. The findings suggest an opportunity for Extension and farmer-serving agencies to provide innovative communication, programming and support designed to address the unique struggles of urban farmers.
Keywords: urban farmers; urban food production; urban agriculture; Extension education; Q methodology; Extension